Bridging the Gap - Geovana-Albertina ZOICAN (Annals of the University of Craiova for Journalism, Communication and Management, 2025)
This article explores the interplay between communication and negotiation through a contemporary lens. Drawing from both theory and applied frameworks, it highlights the five critical stages of negotiation, the practical competencies needed by modern negotiators, and the impact of digital transformation on negotiation dynamics. Through this analysis, negotiation is framed not merely as a strategic tool, but as a deeply human and relational process – where empathy, ethics, and adaptability define success.